2012
DOI: 10.1177/0310057x1204000508
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Interruptions of Anaesthesia Providers using Predictions of Workload from Anaesthesia Information Management System Data

Abstract: Perioperative interruptions generated electronically from anaesthesia information management systems (AIMS) can provide useful feedback, but may adversely affect task performance if distractions occur at inopportune moments. Ideally such interruptions would occur only at times when their impact would be minimal. In this study of AIMS data, we evaluated the times of comments, drugs, fluids and periodic assessments (e.g. electrocardiogram diagnosis and train-of-four) to develop recommendations for the timing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 28 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Such decision-making is based not simply on having displays showing data from the AIMS such as real-time usage 63-65 but displays with recommendations or displays and brief checklists. [66][67][68][69] Consequently, in our experience, achieving a cost reduction [32][33][34]37,38,42,[44][45][46] depends not only on having a knowledgeable 50 OR Medical Director and someone with an analytics background but also on the Director of Anesthesia Informatics. Many of the AIMS data used for this purpose are the basic signals (e.g., when there is pulse oximetry and heart rate monitoring in use in an OR, the OR is occupied by a patient).…”
Section: Role Of Anesthesia Information Management Systems For Decisimentioning
confidence: 99%
“…Such decision-making is based not simply on having displays showing data from the AIMS such as real-time usage 63-65 but displays with recommendations or displays and brief checklists. [66][67][68][69] Consequently, in our experience, achieving a cost reduction [32][33][34]37,38,42,[44][45][46] depends not only on having a knowledgeable 50 OR Medical Director and someone with an analytics background but also on the Director of Anesthesia Informatics. Many of the AIMS data used for this purpose are the basic signals (e.g., when there is pulse oximetry and heart rate monitoring in use in an OR, the OR is occupied by a patient).…”
Section: Role Of Anesthesia Information Management Systems For Decisimentioning
confidence: 99%
“…Our anesthesia time is longer than the anesthesia-controlled time, as the latter excludes the period from the start of positioning and surgical draping until incision. We did that because our prior study showed that documentation and other events were completed in 50% of cases by 12 to 13 minutes after the start of the surgical procedure [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…These steps are complete in 50% of cases 12 to 13 minutes after surgical incision, depending on the surgical procedure. Neither surgical time, neuraxial anesthesia, positioning, ambulatory surgery center, or specialty influenced the 12- to 13-minute duration [ 7 ]. Several extra minutes also are needed for the handoff to the relieving provider and for the trip to the lactation room, which may not be close to the surgical suite.…”
Section: Introductionmentioning
confidence: 99%
“…A feared problem with its use may be increased malpractice exposure as some evanescent perioperative physiological changes and the artifactual data from the monitors may be misinterpreted in the event of unfavorable patient outcome. [ 27 28 ] Hence, although introduced almost 25 years ago, its use in clinical practice is still limited, due to which there is no evidence of improved patient outcome with its use.…”
Section: Monitoring Standards In Anesthesiamentioning
confidence: 99%